Perception and preferences of teaching and learning methods in community medicine: a cross sectional study - Joshi, Krishna Prakash; Robins, M.; Yanadi Reddy, M. (International Journal Of Community Medicine And Public Health, 2018)
Background: Knowledge of community medicine plays a very important role in proper and effective delivery of health care services to the society. Every teacher has her or his own style of teaching and now teachers are adjusting their approach depending on their students’ learning needs. The aims and objectives of the study were to assess the perception of 3rd year medical students towards teaching and learning methods in community medicine & to know their preferences among various commonly used teaching learning media & methods. Methods: A cross-sectional descriptive questionnaire-based study was conducted among 3rd year medical students (6th semester) of SVS Medical College, Mahabubnagar, Telangana, India. A pre-designed, pre-tested self-administered questionnaire was used to collect data. Most of the responses were collected as MCQs type & Likert five point scale. The data was analyzed by calculating percentage. Results: Out of total 140 participants 42 (30%) were boys and 98 (70%) were girls. All were within the age group of 21-24years. Regarding the preference of teaching aid, PPT was preferred by maximum 37% participants followed by combination of CB & PPT (30%), Chalk & board (29%). Student’s preference about current T-L methods shows that maximum participants preferred. SGD (34%), followed by interactive lectures (26%). Around 65% students were satisfied & 20% were strongly satisfied with current learning approaches. Conclusions: Small group discussion and blended or interactive teaching are the most preferred learning method when compared with traditional teaching methods indicating that students are more interested in active teaching and learning methods.